Detection prospect of Cherenkov radiation from cosmic rays using a fluorescence detector - Martins, Edyvânia Emily Pereira (2020)
The energy spectrum of cosmic rays is governed by a power law in energy with its spectral index being variable; it is also understood that above 4 × 1019 eV a suppression on the incoming flux is present. The composition can only be directly measured up to about 1014 eV with satellite and balloon-borne experiments. At greater energies, the study of cosmic rays occurs through the detection of air showers and the inference of the primary particles (or nucleus\') information by comparing the data to shower simulations, which in its turn depends heavily on the chosen hadronic interaction model. The evaluation of Cherenkov light emitted by the passage of an incoming nucleus through the atmosphere reduces the dependence on hadronic interaction models to recover information on the primary. We investigate in this work the detection prospect of such direct Cherenkov photons by the fluorescence telescopes at the Pierre Auger Observatory. Simulations using the Monte Carlo method were developed to forecast the number of photons produced by an iron nucleus, as well as their distribution at ground level, for different energies, incidence angles, and distance of the shower core to the telescope. A simple simulation on the main aspects of the measurement procedure was carried out taking into account the telescopes limited field of view and the signal to noise ratio. The study culminates in the expected number of events to be detected per year at the Auger Observatory, given distinct iron nuclei concentration scenarios on the all-particle flux of cosmic rays.